Konsistenz oder Widerspruch? Mobilitätsbezogene Einstellungen und die Verkehrsmittelnutzung der jungen ‚New Generation‘ - Konrad, Kathrin; Groth, Sören (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
In this paper, we examine the role of mobility-related attitudes in the travel mode use of young people, the extent to which young adults and teenagers behave consistently in relation to their attitudes, and the conditions on which the consistency of attitudes and behaviour depends. We thus continue the current discussion about the loss of importance of the car for young people in which various socio-demographic trends, but also changed attitudes, are used as explanatory factors, especially on a hypothetical level. Our contribution closes a research gap in that so far neither the relationship between attitudes and behaviour among young people has been empirically investigated nor has this relationship been empirically placed in a context of spatial, economic and socio-demographic conditions. We address this by means of differentiated correlation analyses and the calculation of correlation differences on the basis of a nationwide German survey of young people from 2013. This enables us to demonstrate that young people basically behave consistently in line with their attitudes. However, there are significant differences which confirm that certain spatial, economic and socio-demographic conditions are essential for the implementation of attitudes into corresponding travel mode use.
Keywords: Young people; new generation; loss of car importance; altered mode-related attitudes; travel mode use; end of the automobile society